2017
DOI: 10.1177/0954408917738488
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure jet-assisted turning of AISI 304: Experimental and multi-objective optimization approach

Abstract: High-pressure jet-assisted turning is an effective method to decrease the cutting force and surface roughness. Efficiency of this process is related to application of proper jet pressure proportional to other process parameters. In this research, experiments were conducted for high-pressure jet-assisted turning in finishing AISI 304 austenitic stainless steel, based on response surface method. Against the expectations, the maximum jet pressure could not lead to the most efficient results, which means that appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Zhuang et al [ 20 ] indicated that the residual stresses rise as the tool edge radius increases. Electroplusing [ 21 ], high-pressure jet [ 22 ], and liquid nitrogen [ 23 ]-assisted turning effectively reduce the surface roughness of AISI 304. In various nanofluid-assisted turning AISI 304 stainless steel, advantages were observed in terms of surface roughness, cutting forces, turning temperature, and flank wear [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhuang et al [ 20 ] indicated that the residual stresses rise as the tool edge radius increases. Electroplusing [ 21 ], high-pressure jet [ 22 ], and liquid nitrogen [ 23 ]-assisted turning effectively reduce the surface roughness of AISI 304. In various nanofluid-assisted turning AISI 304 stainless steel, advantages were observed in terms of surface roughness, cutting forces, turning temperature, and flank wear [ 24 ].…”
Section: Introductionmentioning
confidence: 99%